The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.4049/jimmunol.179.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Autoantigen Ro52 Is an Interferon Inducible E3 Ligase That Ubiquitinates IRF-8 and Enhances Cytokine Expression in Macrophages

Abstract: IFN regulatory factor (IRF)-8 is a transcription factor important for the development and function of macrophages. It plays a critical role in the induction of cytokine genes, including IL-12p40. Immunopurification and mass spectrometry analysis found that IRF-8 interacted with Ro52 in murine macrophages upon IFN-γ and TLR stimulation. Ro52 is an IFN-inducible protein of the tripartite motif (TRIM) family and is an autoantigen present in patients with Sjögren’s syndrome and systemic lupus erythematosus. Ro52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
176
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(184 citation statements)
references
References 26 publications
4
176
1
3
Order By: Relevance
“…Deletion of the SPRY domain in TRIM11, TRIM21, and TRIM25 abrogated the interaction of the proteins with their binding partner proteins. 26,32,33 In this study we found that the SPRY domain was essential for the nuclear localization of TRIM22, and TRIM22 lacking the SPRY domain was localized exclusively to the cytoplasm of HepG2 cells and lost its suppressive activity on HBV CP. As no nuclear localization signal (NLS) is found in the SPRY domain of TRIM22 and the SPRY domain has often been implicated in protein-protein interactions, we suspect that TRIM22 may be transported into the nucleus by binding to other nuclear proteins through its SPRY domain.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Deletion of the SPRY domain in TRIM11, TRIM21, and TRIM25 abrogated the interaction of the proteins with their binding partner proteins. 26,32,33 In this study we found that the SPRY domain was essential for the nuclear localization of TRIM22, and TRIM22 lacking the SPRY domain was localized exclusively to the cytoplasm of HepG2 cells and lost its suppressive activity on HBV CP. As no nuclear localization signal (NLS) is found in the SPRY domain of TRIM22 and the SPRY domain has often been implicated in protein-protein interactions, we suspect that TRIM22 may be transported into the nucleus by binding to other nuclear proteins through its SPRY domain.…”
Section: Discussionmentioning
confidence: 82%
“…1A). 11,[26][27][28] To further investigate whether TRIM22 was induced in an IFN-dependent manner, we examined the expression level of TRIM22 protein by western blot using anti-TRIM22 antibody in HepG2 cells stimulated with IFN-␣ or IFN-␥. As shown in Fig.…”
Section: Expression Of Trim Family Molecules In Ifn-mentioning
confidence: 99%
“…Both TRIM27 and TRIM21 have been shown to interact with the IKKs repressing their activity and as a result pro-inflammatory cytokine production [27,88]. TRIM21 also interacts with the IRFs 3, 7,8, each interaction resulting in repression of NFKB and IFN promoter activity [85,[109][110][111]. On the contrary, some TRIMs function as positive regulators of these pathways.…”
Section: Figure Legendsmentioning
confidence: 99%
“…Additional targets for Ro52/TRIM21 have been reported -IRF8 for example is positively regulated by Ro52/TRIM21 ubiquitination, resulting in modest increases in IL8-dependent cytokine production [85]. In a separate study Ro52/TRIM21 has been demonstrated to stabilise IRF3 levels and therefore positively regulates IRF3 activity during antiviral responses [86].…”
Section: Regulation Of Transcriptional Responsesmentioning
confidence: 99%
“…TRIM21 has been reported to ubiquitinate IRF3, IRF5, IRF7, and IRF8 (9,(15)(16)(17)(18), thus affecting the expression of IRF target genes such as IFNb, IL-6, and IL-12/IL-23 p40. Two independent studies demonstrate that Trim21 2/2 cells overexpress proinflammatory cytokines after TLR activation in vitro (8,9).…”
mentioning
confidence: 99%